Effect of Ni and Sr additions on the microstructure, mechanical properties, and coefficient of thermal expansion of Al-23%Si alloy. (2021) - Vijayan, Vijeesh; Ravi, M.; Prabhu, K Narayan
Abstract: In this paper, the combined and individual effect of strontium (Sr) and nickel (Ni) additions on the microstructure and mechanical properties of hypereutectic Al-23Si alloy was studied using an optical microscopy, universal tensile testing machine and Brinell hardness tester. The wear properties and coefficient of thermal expansion of the melt treated samples were determined using pin on disc wear testing machine and linear expansion measurement unit respectively. The results indicate that the Ni additions significantly enhanced the mechanical properties of the alloy, whereas, presence of Sr was detrimental. It was observed that the improvement in mechanical properties due to Ni was primarily due to refinement and transformation of the star shaped primary silicon into polyhedral crystals. However, the addition of Sr, both as separate and when combined with Ni, transformed the primary silicon into a faceted crystal and hence decreased the mechanical property. Among all, the Ni melt treated alloy samples showed lowest wear rate and coefficient of thermal expansion.